Isu dan cabaran yang mempengaruhi tahap pembangunan kerjaya organisasi di kalangan pegawai JPJ Alor Setar, Kedah - Ali, Abdul Rahim (2021)
This study aims to look at the issues and challenges that affect the level of organizational career development among members of the Jabatan Pengangkutan Jalan (JPJ). Recently, the issue of career development among the public sector, especially among enforcement personnel has become a hot topic, including in JPJ. Therefore, researcher would like to see the need for a study to look at issues and challenges among JPJ members on career development in JPJ Alor Setar, Kedah. Researcher believe there will be issues, challenges and factors that contribute to career development among members. The objective of this thesis is to identify the level of understanding and knowledge of career development and the key factors that contribute to career development. Researcher also wanted to identify the relationship between work culture and the ruling party with career development among members. The final objective of this thesis is to see the challenges faced by JPJ in implementing career development programs among members. This thesis uses the Kaedah Temubual Berkumpulan (KTB) with the First Group consisting of 10 informants among JPJ members from various ranks while the Second Informant Group consists of 5 JPJ officers who clearly support the results of the First Informant Group interviews. Interviews among informants were conducted for 3 months. The results showed that the informants had a good understanding and knowledge of career development practices in JPJ. Although the informants came from various ranks, it did not affect the understanding of career developers. The results of the study also found a significant relationship between the Parsons Model and Factor Trait that connects the elements of dominant and mediating factors with career development among members in JPJ. However, there are also interview results that show that there are a few informants who feel that career development programs are less effective and transformation in the promotion process needs to be improved from time to time. In summary, all the objectives and questions of the study were clearly answered through the results of the interviews conducted. Looking at the results of the study, some suggestions for improvement expressed with JPJ can collaborate with consultants in the public or private sector in evaluating the existing system in order to improve career development among members in accordance with the demands of work as an enforcement member.